The Degree Of Availability Of Emotional Intelligence Among Faculty Members At Yarmouk University (International Journal of Environmental Sciences, 2025)
The study aimed to identify the degree of availability of emotional intelligence among faculty members at Yarmouk University, and the study used the descriptive approach, and a questionnaire consisting of (17) items as a tool for data collection, and the study sample reached (350) faculty members at Yarmouk University, and the results revealed that the degree of availability of emotional intelligence among faculty members was high, and there were no statistically significant differences in the degree of availability of emotional intelligence attributed to the variables of the study (gender, college, academic rank, and years of experience). The study recommended maintaining the high level of emotional intelligence among faculty members at Yarmouk University in the areas of (emotion management, emotion regulation, and emotional knowledge).